Standardized image documentation in nuclear medicine - Bohuslavizki, Karl H. (Radiology and oncology (Ljubljana), 1999)
There are no generally accepted standards for image documentation in every daynuclear medicine practice. This is a problem whenever hardcopies from othercenters are to be re-interpreted or compared to present images of the same patient. In order to support image reading by a third party proposals of documentation necessary within images are elaborated. Examples of image documentation of the most frequently performed nuclear medicine studies are given, i.e. lung scintigraphy, thyroid scintigraphy, bone scintigraphy both inplanar and in SPECT-technique, renal function scintigraphy, myocardial perfusion scintigraphy, and positron emission tomography. These, examples are intendent to stimulate discussion within the nuclear medicine community about the content of documentation necessary in nuclear medicine images.
Keywords: Diagnostic imaging; Medical records; Nuclear medicine; Radionuclide imaging; Standards; Tomography, emission-computed, single-photon